2013
DOI: 10.2319/071113-507.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the publications in three major orthodontic journals: A comparative analysis of two 5-year periods

Abstract: The publications from 1998-2002 and 2008-2012 were significantly different both in terms of numbers and characteristics. Within 2008-2012 there were notable differences between the three journals concerning the type and origin of the publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 28 publications
6
44
0
Order By: Relevance
“…In a bibliometrics study, Mavropoulos and Kiliaridis (4) found that a majority of articles published in orthodontics journals focus on the diagnosis and treatment methods and that studies about novel treatment techniques have markedly decreased in the last two decades, highlighting the increased need for high-quality studies producing reliable evidence. According to the previous studies evaluating the literature of orthodontics between 1998 and 2012, a significant increase was detected in original articles compared with review articles and case reports (5,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a bibliometrics study, Mavropoulos and Kiliaridis (4) found that a majority of articles published in orthodontics journals focus on the diagnosis and treatment methods and that studies about novel treatment techniques have markedly decreased in the last two decades, highlighting the increased need for high-quality studies producing reliable evidence. According to the previous studies evaluating the literature of orthodontics between 1998 and 2012, a significant increase was detected in original articles compared with review articles and case reports (5,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that between 1981 and 2016, the total number of the published orthodontic articles continuously increased (4,5). The features characterizing these publications, such as authorship, demographics, constituent components of affiliation, and origin, provide insight about the current trends on the acceptance of articles for Fundagül Bilgiç 1 publication (6).…”
Section: Introductionmentioning
confidence: 99%
“…Authorship demographics, constituent components of affiliation, origin, basic or applied research and other variables. 2 To assess the research contributions of countries around the world, biomedical research publication has been used as an index for health research productivity. 3 Over the past decade, several studies have evaluated the quantity and quality of biomedical research publications produced around the world.…”
Section: Introductionmentioning
confidence: 99%
“…This has been highlighted by investigations on the characteristics of orthodontic publications, which showed a significantly higher frequency of multi-author teams with affiliations from different scientific disciplines in orthodontic publications within a decade. [2][3] The purpose of this text is to review the advances occurring in the field of research methods of investigating various properties of orthodontic applications of materials, to assist the reader in navigating into this topic; a synopsis of the future of materials is also provided listing future applications, which already exist at experimental stage or are yet unavailable but with the relevant technology already presented in broader scientific disciplines.…”
Section: Introductionmentioning
confidence: 99%